Attitude of Iranian Medical Oncologists Toward Economic Aspects, and Policy-making in Relation to New Cancer Drugs - Rajabali Daroudi; Mehrzad Mirzania; Kazem Zendehdel (Kerman University of Medical Sciences, 2016)
Background Although medical oncologists can have an important role in controlling the cost of cancer treatment, there is little information about their attitudes toward the cost of cancer treatment and the impact of cost on their treatment recommendations, especially in low- and middle-income countries (LMICs). In this study, we assessed the attitude of Iranian medical oncologists toward some economic aspects of new cancer drugs. Methods We translated a questionnaire that was used in similar studies in the United States and Canada into Persian and modified it according to the local setting in Iran. The face and content validity of the questionnaire were assessed by oncologists before being used in the survey. We distributed the questionnaire and collected the data from 80 oncologists who participated in the 13th Annual Congress of the Iranian Society of Medical Oncology and Hematology (ISMOH). Results Fifty-two oncologists participated in our study (a response rate of 65%). The majority of oncologists stated that drug costs and patient out-of-pocket (OOP) costs influence their treatment recommendations (92% and 94%, respectively). Most oncologists (70%) felt that they are ready enough to use cost-effectiveness information in their treatment decisions, and 74% believed that patients should only have access to cancer treatments that are cost-effective. Most oncologists agree that the government should have control over drug prices, and more use of cost‐effectiveness data is required for decision-making about cancer drug coverage. Ninety-one percent of oncologists said that they always or frequently discuss cancer treatment costs with their patients. Oncologists believed that academic groups (research centers and scientific societies) (81%) and the Ministry of Health (MoH) (43%) are the most eligible groups for determining whether a drug provides good value. Conclusion Iranian medical oncologists are ready to participate in the health technology assessment and prioritysetting process. This situation creates a unique opportunity for the government to rely on scientific societies and find an appropriate solution for the improvement of patients' access to high-quality care.